Y +6 = -7/6 (x-4)
Mark brainliest please
Hope this helps you
Answer:
f(x) = 488
Step-by-step explanation:
first you plug in 82 in for x then you multiply by 6 times 82 and you get 492 then you subtract 4 and you get 488
Answer:
JL = 78
Step-by-step explanation:
MN is a midsegment. Based on the midsegment theorem,
MN = ½(JL)
MN = 5x - 16
JL = 4x + 34
Plug in the value
5x - 16 = ½(4x + 34)
5x - 16 = ½*4x + ½*34
5x - 16 = 2x + 17
Collect like terms
5x - 2x = 16 + 17
3x = 33
Divide both sides by 3
x = 11
✔️JL = 4x + 34
Plug in the value of x
JL = 4(11) + 34
JL = 44 + 34
JL = 78
Answer:
D
Step-by-step explanation:
(3, 9) (-3, 5)
0 is in the middle 7 is in the middle
for x: 3 2 1 0 -1 -2 -3 for y: 9 8 7 6 5
Thus, (0, 7) is the midpoint between (3, 9) and (-3, 5)